Interface Test Adapter (ITA) Design for Sequential Testing of Transient Voltage Suppressor Diodes to Reduce Cycle Time - Malabanan, Francis (Archīum Ateneo, 2019)
The advancement in semiconductor circuit design, particularly its miniaturization has increased the circuit sensitivity to electrical stresses. To protect the circuits, transient voltage suppressor (TVS) diodes are used. This device must be tested with the use of high-power tester that is capable to surge high inrush power. In a test manufacturing company that employs manual testing of TVS diodes, the cycle time increases which results to a decrease in the number of unit per hour (UPH). In this study the, the Design for Six Sigma (DFSS) methodology is used to develop an interface test adapter (ITA) that is interconnected between a manual test machine and the unit under test (UUT). The ITA consists of an electromechanical relay (EMR) for switching, a linear actuator for mechanical shifting, and an Arduino-based microcontroller. The ITA is used to automate the testing of eight bidirectional TVS diodes device in a single unit of vertical array package to reduce the test cycle time. This also minimizes human intervention that avoids human handling error and lowers the chances of possible injuries that might happen during the process. Results show that there is sufficient improvement in the test cycle time.